Selective CDK7 inhibition with BS-181 suppresses cell proliferation and induces cell cycle arrest and apoptosis in gastric cancer - Wang, Bo-Yong (Drug Des Devel Ther, 2016)
Cyclin-dependent kinase (CDK) family members have been considered as attractive therapeutic targets for cancer. In this study, we aim to investigate the anticancer effects of a selective CDK7 inhibitor, BS-181, in gastric cancer (GC) cell line. Human GC cells (BGC823) were cultured with or without BS-181 at different concentrations for 24–72 hours. BS-181 significantly reduced the activity of CDK7 with downregulation of cyclin D1 and XIAP in GC cells. Treatment with BS-181 induced cell cycle arrest and apoptosis. The expression of Bax and caspase-3 was significantly increased, while Bcl-2 expression was decreased in cells treated with BS-181. In addition, the inhibition of CDK7 with BS-181 resulted in reduced rates of proliferation, migration, and invasion of gastric cells. Those results demonstrated the anticancer activities of selective CDK7 inhibitor BS-181 in BGC823 cells, suggesting that CDK7 may serve as a novel therapeutic target or the treatment of GC.